Analysis of Formaldehyde in Circulating Grapes in Makassar - Nurfathiyatul Izza; Aminah Aminah; Rais Razak (Pharmaceutical Reports, 2023)
Formalin or formaldehyde is a chemical compound whose use is prohibited as a preservative in food additives. This study aims to analyze the content of formalin in red grapes (Vitis vinifera) circulating in the city of Makassar. The method used in this test is by using Schiff reagent and UV-Vis spectrophotometry. The results of the Schiff reagent test showed that two of the 10 grape samples were positive for formalin. Test results on UV-Vis Spectrophotometry at a wavelength of 556 nm, that all red grape samples obtained contained formalin with formalin levels as follows: Sample Tamalanrea 1 TD = 0.778%, Tamalanrea 2 TD = 0.483%, Manggala TD= 0.452%, Tamalate TD= 0.734%, Biringkanaya TD= 0.552%, Tamalanrea 1 SD= 0.452%.